THE NATURE OF ULTRASTRUCTURAL CHANGES INDUCED BY ORCHIEPIDIDYMITIS IN THE MEN’S TESTES AND EJACULATE - Hlodan, O.Ya.; Hrytsuliak, B.V.; Hrytsuliak, V.B.; Ivasiuk, I.Y. (World of Medicine and Biology, 2020)
In 14 testicular biopsy specimens of men with male infertility, who had orchiepididymitis, aged 22-35 years we studied the nature of ultrastructural changes and their effect on ejaculate values. There were determined: deformity and pycnosis of nuclei, uneven expansion of perinuclear space, cytoplasm vacuolization, homogenization of mitochondrial cristae, expansion of endoplasmic reticulum cisterns and elements in the Golgi apparatus in endothelial cells of the hemocapillaries, peritubular myoid cells of the coiled seminiferous tubules lining, Sertoli cells, spermatocytes and spermatids, which were complemented in the ejaculate with reducing twice the sperm concentration in 1 ml, increasing 3 times the number of pathological forms and reducing the sperm motility.